2011
DOI: 10.1007/s12610-011-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone in the central control of penile erection

Abstract: Résumé La testostérone orchestre l’organisation périnatale et l’activation adulte des structures nerveuses cérébrales et spinales impliquées dans l’expression du comportement sexuel mâle. Cette revue décrit brièvement les différents effets de la testostérone dans la régulation de la motivation sexuelle et de l’érection, et les modèles génétiques générés, jusqu’à présent, dans le but d’élucider ses mécanismes d’action centraux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…Nitric oxide is a signaling molecule that is involved in inflammation and immunological processes [29] but it has also a key role in the erection mechanism [30,31]. It is the main mediator of penile erection because of its involvement in the relaxation of the penile smooth muscle, thus in the penile erection [32,33]. Results showed that compared to the control, all extracts stimulated the release of NO in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is a signaling molecule that is involved in inflammation and immunological processes [29] but it has also a key role in the erection mechanism [30,31]. It is the main mediator of penile erection because of its involvement in the relaxation of the penile smooth muscle, thus in the penile erection [32,33]. Results showed that compared to the control, all extracts stimulated the release of NO in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%